Reversible transformation between CsPbBr3 and Cs4PbBr6 nanocrystals. Issue 34 (3rd August 2018) - Li, Yanxiu; Huang, He; Xiong, Yuan; Kershaw, Stephen V.; Rogach, Andrey L.
Abstract : We introduce both phase and morphology reversible transformation between CsPbBr3 and Cs4 PbBr6 nanocrystals where the cubic morphology of the former is preserved. Abstract : A reversible transformation between CsPbBr3 and Cs4 PbBr6 nanocrystals through a simple treatment with extra ligands or PbBr2 (for the reverse direction) is reported. These transformations are so far the first report of direct reversibility, without a net change in morphology, between CsPbBr3 and Cs4 PbBr6 and then back to CsPbBr3 nanocrystals, which provides a mechanism for flexible reorganization of the lead halide perovskite lattice.